ENHANCING THE ACCESSIBILITY OF RAILWAY TRANSPORTATION FOR INDIVIDUALS WITH PHYSICAL DISABILITIES - Paulina GAJEWSKA; Irena SZEWCZYK; Georgios KOULOURIS (Transport Problems)
The purpose of public mass transport is the general accessibility for all of its users. The lack of (or insufficient adjustment of) the tourist transport infrastructure to the needs of persons with disabilities and seniors is an obstacle to their free movement. The aim of this article is to determine to what extent the railway infrastructure is adjusted to the needs of disabled persons and what problems these persons struggle with most frequently. The aim of this article is to determine and discuss various aspects of disability. The primary research method used in the paper is the Failure Mode and Effects Analysis (FMEA), which is a method used to assess the state of adaptation of the station for people with disabilities. The purpose of the tests is to identify existing and potential defects as well as their causes and effects. Research results verify the degree of adaptation of rail transport for people with disabilities and have diagnostic value. Future research should focus on the full usability of transport infrastructure for people with disabilities. The results of the current research have a number of practical implications, mainly for people involved in the transport industry. Building awareness regarding problems related to the mobility of people with disabilities, sensitize to the needs and challenges of such people has significant social implications. This paper has cognitive value for the development of knowledge, science, and quality in terms of adapting transport for people with disabilities. To achieve the study’s purpose, the FMEA was conducted on the example of the main railway station in Bielsko-Biała, Poland. Suggestions were also formulated to allow persons with disabilities to use railway transport to a greater extent.